Perancangan dan Implementasi Sistem Gameplay pada Game Pixel Art Jejak Pagaruyung sebagai Media Interaktif Pengenalan Budaya Minangkabau - Mohammad Exsha Baguna; Sheanny Ocmi Sakti (Lembaga Yasin AlSys, 2026)
Although the development of culturally themed digital games has continued to grow, studies that position gameplay systems as the primary means of conveying cultural information remain limited. This study aimed to design and implement a gameplay system in the pixel-art game Jejak Pagaruyung as an interactive medium for introducing Minangkabau culture. The study employed a descriptive-evaluative product development approach using the Multimedia Development Life Cycle model, which comprised the conceptualization, design, material collection, production, and testing stages. Data were collected through direct observation at Istana Basa Pagaruyung, documentation, functional testing, observation of gameplay experiences, brief interviews, and questionnaires administered to users aged 12–25 years. The data were analyzed descriptively by categorizing qualitative findings and examining the functional testing results. The results showed that movement systems, object interactions, non-player character dialogues, minigames, mission stages, portals, audio, and transitions were successfully integrated using Godot Engine and GDScript. All 11 tested components functioned as designed, with no critical errors identified. Five rooms, six non-player characters, five minigames, and cultural objects, such as keris, carano, and tingkuluak, created a structured cultural exploration experience. This study produced a practical model for integrating narratives, cultural objects, interactive activities, and game progression as a medium for introducing Minangkabau culture. Further testing is required to empirically measure the effectiveness of the game in improving cultural understanding.